Heterozygous Germline Mutations in the CBL Tumor-Suppressor Gene Cause a Noonan Syndrome-like Phenotype - Martinelli, Simone; De Luca, Alessandro; Stellacci, Emilia; Rossi, Cesare; Checquolo, Saula; Lepri, Francesca; Caputo, Viviana; Silvano, Marianna; Buscherini, Francesco; Consoli, Federica; Ferrara, Grazia; Digilio, Maria C.; et al. (American journal of human genetics, 2010)
RAS signaling plays a key role in controlling appropriate cell responses to extracellular stimuli and participates in early and late developmental processes. Although enhanced flow through this pathway has been established as a major contributor to oncogenesis, recent discoveries have revealed that aberrant RAS activation causes a group of clinically related developmental disorders characterized by facial dysmorphism, a wide spectrum of cardiac disease, reduced growth, variable cognitive deficits, ectodermal and musculoskeletal anomalies, and increased risk for certain malignancies. Here, we report that heterozygous germline mutations in CBL, a tumor-suppressor gene that is mutated in myeloid malignancies and encodes a multivalent adaptor protein with E3 ubiquitin ligase activity, can underlie a phenotype with clinical features fitting or partially overlapping Noonan syndrome (NS), the most common condition of this disease family. Independent CBL mutations were identified in two sporadic cases and two families from among 365 unrelated subjects who had NS or suggestive features and were negative for mutations in previously identified disease genes. Phenotypic heterogeneity and variable expressivity were documented. Mutations were missense changes altering evolutionarily conserved residues located in the RING finger domain or the linker connecting this domain to the N-terminal tyrosine kinase binding domain, a known mutational hot spot in myeloid malignancies. Mutations were shown to affect CBL-mediated receptor ubiquitylation and dysregulate signal flow through RAS. These findings document that germline mutations in CBL alter development to cause a clinically variable condition that resembles NS and that possibly predisposes to malignancies.